Five-year motor functional outcome in children with acquired brain injury. Yet to the end of the story?. (3rd October 2018) - Beretta, Elena; Molteni, Erika; Galbiati, Sara; Stefanoni, Giuseppe; Strazzer, Sandra
ABSTRACT: Purpose : The description of motor changes and clinical evolution of a pediatric cohort with acquired brain injury (ABI) over 5 years by the functional independence measure for children (WeeFIM). Methods : We analyzed retrospective data from 496 patients (aged 0–18 years) with severe ABI admitted for rehabilitation. WeeFIM scores and disability rating scale (reference scale) were collected at admission, discharge and yearly, up to year 5. Results : Functional limitations gradually reduced after ABI, but children still had residual disabilities at the endpoint. Seventeen percent of patients demonstrated no improvement at WeeFIM. Gait analysis showed that decreased WeeFIM scores in the mobility domain are associated with slower and shorter steps, and increased step width, compensating for imbalance. Conclusions : Five years after ABI, improvement is still found in the mobility domain of WeeFIM. This work adds evidence that margin still exists at least until year 5 after injury for profitably continuing the rehabilitation effort.